Digital Customer Relationship Management in Improving Service Quality Through E-Commerce Systems - Martowinangun, Kasino; Pasaribu, Johni Setiady; Nurdin, Jusuf (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
Digital Customer Relationship Management (d-CRM) is an evolution of traditional CRM that focuses on the use of digital technology to manage customer relationships. In the context of e-commerce, “d-CRM” is a very important role in improving service quality through personalization, automation, and deeper utilization data of customers. This paper aims to explore how “d-CRM” can be applied in e-commerce platforms to improve service quality, customer satisfaction, and loyalty. By reviewing a case study on CV Bintang Raya Plastik and the literature, this article highlights the benefits of “d-CRM” and the challenges it in implementation.